Staphylococcus succinus 14BME20 Prevents Allergic Airway Inflammation by Induction of Regulatory T Cells via Interleukin-10 - Song, Jisun; Lim, Hui Xuan; Lee, Arim; Kim, Soojung; Lee, Jong-Hoon; Kim, Tae Sung (Frontiers in Immunology, 2019)
Asthma is a common chronic inflammatory disease, which is characterized by airway hyperresponsiveness (AHR), high serum levels of immunoglobulin (Ig)E, and recruitment of various inflammatory cells such as eosinophils and lymphocytes. Korean traditional fermented foods have been reported to exert beneficial effects against allergic diseases such as asthma and atopic dermatitis. In this study, we investigated whether Staphylococcus succinus strain 14BME20 (14BME20) isolated from doenjang, a traditional high-salt-fermented soybean food of Korea, exerts suppressive effects on allergic airway inflammation in a murine model. Mice were orally administered with 14BME20, then sensitized and challenged with ovalbumin as an allergen. Administration of the 14BME20 significantly suppressed AHR and influx of inflammatory cells into the lungs and reduced serum IgE levels. Moreover, the proportion of T helper type 2 (Th2) cells and the production of Th2 cytokines were decreased in 14BME20-treated mice, whereas dendritic cells (DCs) with tolerogenic characteristics were increased. In contrast, oral administration of 14BME20 increased the proportion of CD4+CD25+Foxp3+ regulatory T (Treg) cells and the level of interleukin (IL)-10 in 14BME20-treated mice. Furthermore, 14BME20 induced maturation of tolerogenic DCs, and 14BME20-treated DCs increased Treg cell population in a coculture system of DCs and CD4+ T cells. The addition of a neutralizing anti-IL-10 mAb to the culture of cells that had been treated with 14BME20 decreased the enhanced Treg cell population, thereby indicating that 14BME20-treated DCs increase Treg cell population via DC-derived IL-10. These results demonstrate that oral administration of 14BME20 suppresses airway inflammation by enhancing Treg responses and suggest that the 14BME20 isolated from doenjang may be a therapeutic agent for allergic asthma.